A treatment method and system for degrading perfluorooctanoic acid in water

By using composite photocatalytic degradation of perfluorooctanoic acid is solved, and the efficiency of photocatalytic degradation of perfluorooctanoic acid and frequent photocatalyst replacement is achieved, and the effect of efficient removal of perfluorooctanoic acid and reducing treatment costs is achieved.

CN118993238BActive Publication Date: 2025-03-18HEFEI WATER SUPPLY GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411164949.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-03-18
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

In the prior art, the photocatalytic degradation of perfluorooctanoic acid is relatively low, and the photocatalyst needs to be replaced frequently, resulting in high cost and reduced efficiency.

Method used

Using a composite photocatalyst, which consists of biochar, gallium oxide and carbon quantum dots, is prepared by a silica sphere template to form a hollow structure to improve the reactive site and enhance catalytic efficiency by ultrasonic treatment.

Benefits of technology

The efficiency of photocatalytic degradation of perfluorooctanoic acid is improved, the service life of the photocatalyst is extended, the treatment cost is reduced, and the effect of efficient removal of perfluorooctanoic acid is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993238B_ABST
    Figure CN118993238B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of perfluorooctanoic acid pollutant treatment, and in particular to a treatment method and system for degrading perfluorooctanoic acid in water. The treatment method comprises introducing wastewater to be treated containing perfluorooctanoic acid into a wastewater treatment device, adding a composite photocatalyst and stirring, and treating it under ultraviolet light of 200 to 700 nm for 0.5 to 3 hours. The mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:100 to 1:800; the preparation of the composite photocatalyst comprises: S1, providing a silica sphere template; S2, preparing biochar; S3, biochar deposition; S4, removing the template; S5, gallium oxide loading: S6, carbon quantum dot composite. The present application provides a treatment method and system for degrading perfluorooctanoic acid in water to solve the problem of low efficiency of photocatalytic degradation of perfluorooctanoic acid and repeated replacement of photocatalysts in related technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of perfluorooctanoic acid pollutant treatment, and in particular to a treatment method and system for degrading perfluorooctanoic acid in water. Background Art

[0002] Perfluorooctanoic Acid (PFOA), also known as 15-fluorooctanoic acid, is an organic compound with the chemical formula C8HF 15 O2, which is widely used in industrial and civilian products. Because PFOA has stable physical and chemical properties, is extremely difficult to decompose, and has environmental persistence, bioaccumulation and biological toxicity, it has serious toxic hazards to the liver, nervous system and immune system of humans and animals. Therefore, PFOA has become a new type of persistent organic pollutant after dioxins and organochlorine pesticides.

[0003] In the prior art, the treatment of perfluorooctanoic acid mainly includes physical methods, biological methods, photodegradation methods, etc. Among them, physical methods such as adsorption and membrane separation only transfer perfluorooctanoic acid, and cannot completely remove perfluorooctanoic acid, and are prone to secondary pollution; the biological method breaks the carbon-fluorine bond of PFOA through the action of enzymes to form low molecular weight organic matter, but the degradation cycle is long and there is a problem of incomplete degradation; the photodegradation method uses ultraviolet light or sunlight to make PFOA molecules absorb light energy and then undergo photochemical reactions, resulting in the breaking of chemical bonds, thereby decomposing into small molecular organic or inorganic substances.

[0004] Among them, photocatalytic technology can achieve the degradation of perfluorooctanoic acid under relatively mild conditions, with low energy consumption and simple operation, and has good application prospects. However, it is greatly affected by light intensity and wavelength, and requires a long reaction time. Therefore, it is often necessary to use it with a photocatalyst to achieve better photocatalytic oxidation degradation and improve degradation efficiency. However, the photocatalyst in the related technology may be deactivated, poisoned or structurally damaged during long-term use, resulting in a decrease in catalytic efficiency. Summary of the invention

[0005] The present application provides a treatment method and system for degrading perfluorooctanoic acid in water, so as to solve the problem in the related art that the efficiency of photocatalytic degradation of perfluorooctanoic acid is low and the photocatalyst needs to be repeatedly replaced.

[0006] In a first aspect, a method for degrading perfluorooctanoic acid in water is provided, which comprises the following steps:

[0007] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and treated under ultraviolet light of 200 to 700 nm for 0.5 to 3 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:100 to 1:800;

[0008] The preparation of the composite photocatalyst comprises the following steps:

[0009] S1, providing a silica sphere template;

[0010] S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 400-700° C. for 3-6 hours to obtain biochar precursor powder;

[0011] S3, biochar deposition: the biochar precursor powder is dispersed in deionized water at a mass volume ratio of 1:6 to form a biochar suspension, the silica sphere template is added to the biochar suspension, ultrasonically stirred for 3 to 6 hours, dried at 80 to 100° C. for 12 hours, and carbonized at 500-900° C. to obtain silica spheres covered with a biochar shell;

[0012] S4, removing the template: immersing the silica balls covered with the biochar shell layer in a 8-20 wt% hydrofluoric acid solution, standing at 25° C. for 0.5-1 h, filtering to obtain biochar solids, washing the biochar solids with deionized water, and drying to obtain biochar balls;

[0013] S5. Gallium oxide loading:

[0014] S501, preparing a gallium oxide precursor solution: dissolving gallium nitrate in deionized water at a mass volume ratio of 1:20 to 1:80 to obtain a gallium oxide precursor solution;

[0015] S502, immersing the biochar balls in a gallium oxide precursor solution at a mass volume ratio of 1:3 to 1:6, and treating at 800 to 1000° C. for 3 to 4 hours under a nitrogen atmosphere to obtain gallium oxide-loaded biochar balls;

[0016] S6, Carbon quantum dot composite:

[0017] Preparation of CQDs solution: adding CQDs powder into deionized water at a mass volume ratio of 1:1 to 1:2 to obtain a CQDs solution;

[0018] The gallium oxide-loaded biochar balls and the CQDs solution are ultrasonically mixed for 0.5 to 2 hours, and dried at 80° C. to obtain a composite photocatalyst.

[0019] Preferably, in S1, the preparation of silica spheres comprises the following steps:

[0020] S101, dissolving 0.5-1 mol / L of ethyl orthosilicate in ethanol at a ratio of 1:10 to obtain a transparent solution;

[0021] S102, adding ammonia water to the transparent solution, adjusting the pH to 9-11, stirring at 60° C. for 6-24 hours to obtain a silica sol;

[0022] S103, aging the sol for 24 to 36 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0023] Preferably, the S2 further comprises the following steps:

[0024] S201. Modifying the surface of biochar: mixing the biochar precursor powder with 0.1 mol / L potassium persulfate solution at a mass volume ratio of 1:10 and stirring, stirring at 60° C. for 4 to 6 hours, washing and drying to obtain a modified biochar precursor powder.

[0025] Preferably, the S2 further includes:

[0026] The biochar precursor powder was passed through a 200-mesh sieve.

[0027] Preferably, after S2, the step further includes adding straw fiber to the biochar precursor powder:

[0028] The rice straw fibers are cleaned and dried, and the dried rice straw fibers are ground to pass through a 200-mesh sieve to obtain pretreated rice straw fibers. The method for preparing the rice straw fibers comprises:

[0029] Pyrolyzing the pretreated rice straw fiber at a high temperature of 200-400° C. for 2 h in an oxygen-deficient environment to obtain rice straw fiber powder;

[0030] The straw fiber powder and the biochar precursor powder are mixed in a mass ratio of 1:5 to 1:8, and stirred for 5 minutes to obtain a mixed precursor powder.

[0031] Preferably, it also includes modifying the rice straw fiber:

[0032] The straw fiber powder was mixed with 1 mmol / L hydrogen peroxide solution in a mass volume ratio of 1:10, stirred at 60° C. for 10 min, filtered, washed with deionized water, and dried to obtain modified straw fiber powder.

[0033] Preferably, when the composite photocatalyst is added, an ultrasonic generator is used to emit ultrasonic waves to the wastewater to be treated for ultrasonic treatment, and the sound frequency of the ultrasonic generator is 20 to 100 kHz.

[0034] In a second aspect, a treatment system for degrading perfluorooctanoic acid in water is provided, which is used to implement any one of the treatment methods for degrading perfluorooctanoic acid in water as claimed in claims 1 to 7, characterized in that it comprises:

[0035] The wastewater treatment device comprises a wastewater treatment chamber for containing wastewater to be treated, a feeding module for adding a composite photocatalyst, a stirring module for stirring the wastewater, and an ultraviolet light module, wherein the feeding module, the stirring module and the ultraviolet light module are connected to a power source.

[0036] Preferably, the wastewater treatment device further comprises an ultrasonic module, and the ultrasonic module is connected to the power supply.

[0037] The beneficial effects of the technical solution provided by this application include:

[0038] The embodiment of the present application provides a treatment method and system for degrading perfluorooctanoic acid in water, wherein the biochar is fully wrapped on the surface of the template by using silica balls as a template, and a stable shell is formed by high-temperature heat treatment. After the silica template is removed by using hydrofluoric acid, a hollow biochar is formed; the hollow structure provides a larger internal space and more reactive sites, which is beneficial to the adsorption and degradation of pollutants, and is also beneficial to the loading of gallium oxide and carbon quantum dots;

[0039] The loaded carbon quantum dots can absorb and convert light energy to generate photogenerated electrons and holes due to their unique electronic structure, optical properties and good conductivity, and can also serve as channels for electron transmission. When the carbon quantum dots are combined with gallium oxide, these photogenerated electrons and holes are effectively separated and transferred at the interface, and the rapid extraction of photogenerated electrons in gallium oxide is promoted, reducing the recombination of electrons and holes, thereby enhancing the photocatalytic performance of gallium oxide and improving the photocatalytic efficiency. On the other hand, the composite photocatalyst uses biochar as a carrier, which can enhance the strength of the photocatalyst itself and reduce costs. Therefore, it can solve the problems of low efficiency in photocatalytic degradation of perfluorooctanoic acid and the need for repeated replacement of photocatalysts in related technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 A flow chart of the preparation method of the composite photocatalyst provided in this application;

[0042] Figure 2A flow chart for the preparation of silica spheres provided in this application;

[0043] Figure 3 A schematic diagram showing the degradation rate of perfluorooctanoic acid in the treatment method for degrading perfluorooctanoic acid in water provided in Example 3, Example 4 and Comparative Example 1 of the present application;

[0044] Figure 4 Block diagram of the treatment system for degrading perfluorooctanoic acid in water provided in this application. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0046] See also Figures 1 to 4 As shown, the present application provides a treatment method for degrading perfluorooctanoic acid in water, which can solve the problem of low efficiency of photocatalytic degradation of perfluorooctanoic acid and repeated replacement of photocatalysts in related technologies. The method comprises the following steps:

[0047] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 200 to 700 nm for 0.5 to 3 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:100 to 1:800.

[0048] In some embodiments, when the composite photocatalyst is added, an ultrasonic generator is used to emit ultrasonic waves to the wastewater to be treated for ultrasonic treatment, and the sound frequency of the ultrasonic generator is 20 to 100 kHz.

[0049] Wherein, the preparation of the composite photocatalyst comprises the following steps:

[0050] S1. Provide a silica sphere template.

[0051] It includes the following steps:

[0052] S101, dissolving 0.5-1 mol / L tetraethyl orthosilicate (TEOS) in ethanol at a ratio of 1:10 to obtain a transparent solution;

[0053] S102, adding ammonia water to the transparent solution, adjusting the pH to 9-11, stirring at 60° C. for 6-24 hours to obtain a silica sol;

[0054] S103, aging the sol for 24 to 36 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0055] S2. Preparation of biochar: Using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high-temperature pyrolysis under anoxic conditions at 400-700° C. for 3-6 hours to obtain biochar precursor powder.

[0056] Biochar itself has a large specific surface area, rich pore structure and good stability, and straw has a low cost and can be used as a carrier.

[0057] In some embodiments, S2 further includes the following steps:

[0058] S201. Modifying the surface of biochar: mixing the biochar precursor powder with 0.1 mol / L potassium persulfate solution at a mass volume ratio of 1:10 and stirring, stirring at 60° C. for 4 to 6 hours, washing and drying to obtain a modified biochar precursor powder.

[0059] In some embodiments, the biochar precursor powder is sieved through a 200-mesh sieve.

[0060] In some embodiments, after S2, the step further includes adding straw fiber to the biochar precursor powder:

[0061] The rice straw fibers are only washed and dried, and the dried rice straw fibers are ground to pass through a 200-mesh sieve to obtain pretreated rice straw fibers;

[0062] Pyrolyzing the pretreated rice straw fiber at a high temperature of 200-400° C. for 2 h in an oxygen-deficient environment to obtain rice straw fiber powder;

[0063] The straw fiber powder and the biochar precursor powder are mixed in a mass ratio of 1:5 to 1:8, and stirred for 5 minutes to obtain a mixed precursor powder.

[0064] Specifically, plant fibers themselves have porosity and a large specific surface area. After being added to plant fibers, they can effectively improve the mechanical strength of biochar, making the subsequent biochar balls used as carriers more stable and durable during the processing process, reducing wear and breakage, and reducing the breakage rate, so that the composite photocatalyst can be reused many times and reduce costs.

[0065] Preferably, the step further comprises modifying the rice straw fiber:

[0066] The straw fiber powder was mixed with 1 mmol / L hydrogen peroxide solution in a mass volume ratio of 1:10, stirred at 60° C. for 10 min, filtered, washed with deionized water, and dried to obtain modified straw fiber powder.

[0067] Specifically, the modified rice straw fiber has more oxygen-containing functional groups on its surface and its hydrophilicity is enhanced, which is conducive to its contact and reaction with pollutants such as perfluorooctanoic acid in aqueous solution, and helps to improve the degradation rate.

[0068] S3, biochar deposition: the biochar precursor powder is dispersed in deionized water at a mass volume ratio of 1:6 to form a biochar suspension, the silica sphere template is added to the biochar suspension, ultrasonically stirred for 3 to 6 hours, dried at 80 to 100° C. for 12 hours, and carbonized at 500-900° C. to obtain silica spheres covered with a biochar shell;

[0069] S4, removing the template: immersing the silica balls covered with the biochar shell layer in 8-20 wt% hydrofluoric acid solution, standing at 25° C. for 0.5-1 h, filtering to obtain biochar solids, washing the biochar solids with deionized water, and drying to obtain biochar balls.

[0070] Specifically, the silica sphere template is etched with hydrofluoric acid to obtain hollow-structured biochar spheres, which provide gallium oxide and carbon quantum dots with a larger internal space and more reaction active sites, which is beneficial to the adsorption and degradation of perfluorooctanoic acid, thereby improving the photocatalytic performance.

[0071] S5. Gallium oxide loading:

[0072] S501, preparing a gallium oxide precursor solution: dissolving gallium nitrate in deionized water at a mass volume ratio of 1:20 to 1:80 to obtain a gallium oxide precursor solution;

[0073] S502, immersing the biochar balls in a gallium oxide precursor solution at a mass volume ratio of 1:3 to 1:6, and treating the solution at 800 to 1000°C for 3 to 4 hours under a nitrogen atmosphere to obtain gallium oxide-loaded biochar balls, that is, the precursor solution is uniformly adsorbed on the surface of the biochar by stirring or ultrasonic dispersion, and the deposition and conversion of the precursor on the surface of the biochar are promoted by controlling the temperature and time; and the gallium nitrate precursor is converted into gallium oxide and a stable shell is formed by heat treating the biochar coated with the gallium nitrate precursor (high temperature calcination).

[0074] Gallium oxide has a wide bandgap (4.8eV), high mechanical strength, is not easily corroded, and is suitable for repeated reuse; biochar itself has a large specific surface area, rich air-space structure and good stability. After the biochar balls are generated, the hollow structure provides a larger internal space and more reaction active sites, which is conducive to the loading of gallium oxide.

[0075] S6, Carbon quantum dot composite:

[0076] S601, preparing a CQDs solution: adding CQDs powder to deionized water at a mass volume ratio of 1:1 to 1:2 to obtain a CQDs solution;

[0077] S602, ultrasonically mixing the gallium oxide-loaded biochar balls with the CQDs solution for 0.5 to 2 hours, and drying at 80° C. to obtain a composite photocatalyst.

[0078] Specifically, carbon quantum dots are a type of zero-dimensional carbon nanomaterials with significant fluorescent properties. Their surface is rich in functional groups, which give them good water solubility and stability. The composite photocatalyst obtained by the compound has strong light absorption ability and photocatalytic performance, which can broaden the spectral response range of gallium oxide itself, that is, absorb light energy in a wider range and produce more active substances. For example, the photogenerated electrons generated by the excitation of gallium oxide are quickly transferred to the surface through carbon quantum dots, undergoing redox reactions with PFOA molecules to achieve their degradation, thereby improving the degradation efficiency of PFOA.

[0079] Example 1

[0080] The processing method provided in this embodiment includes the following steps:

[0081] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 0.5 h, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:100;

[0082] The preparation of the composite photocatalyst comprises the following steps:

[0083] S1. Provide silica sphere template:

[0084] S101, dissolving 10 mL of 0.5 mol / L tetraethyl orthosilicate in 100 mL of ethanol to obtain a transparent solution;

[0085] S102, adding ammonia water to the transparent solution, adjusting the pH to 10, and stirring at 60° C. for 10 h to obtain a silica sol;

[0086] S103, aging the sol for 24 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0087] S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 400° C. for 3 h to obtain biochar precursor powder;

[0088] S3, biochar deposition: 10 g of biochar precursor powder was dispersed in 60 mL of deionized water to form a biochar suspension, the silica sphere template was added to the biochar suspension, ultrasonically stirred for 3 h, dried at 80° C. for 12 h, and carbonized at 500° C. to obtain silica spheres covered with a biochar shell;

[0089] S4, removing the template: immersing the silica balls covered with the biochar shell layer in an 8 wt % hydrofluoric acid solution, standing at 25° C. for 0.5 h, filtering to obtain biochar solids, washing the biochar solids with deionized water, and drying to obtain biochar balls;

[0090] S5. Gallium oxide loading:

[0091] S501, preparing a gallium oxide precursor solution: dissolving 1 g of gallium nitrate in 20 mL of deionized water to obtain a gallium oxide precursor solution;

[0092] S502, immersing 5 g of biochar balls in 15 mL of the gallium oxide precursor solution, treating at 800° C. for 3 h under a nitrogen atmosphere, to obtain gallium oxide-loaded biochar balls.

[0093] S6, Carbon quantum dot composite:

[0094] S601, preparing a CQDs solution: dissolving 10 mg of CQDs powder in 10 mL of deionized water to obtain a CQDs solution;

[0095] S602, ultrasonically mixing the gallium oxide-loaded biochar balls obtained in S502 with the CQDs solution for 0.5 h, and drying at 80° C. to obtain a composite photocatalyst.

[0096] Example 2

[0097] The processing method provided in this embodiment includes the following steps:

[0098] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and treated under ultraviolet light of 700 nm for 1 hour, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:100;

[0099] The preparation of the composite photocatalyst comprises the following steps:

[0100] S1. Provide silica sphere template:

[0101] S101, dissolving 10 mL of 0.5 mol / L tetraethyl orthosilicate in 100 mL of ethanol to obtain a transparent solution;

[0102] S102, adding ammonia water to the transparent solution, adjusting the pH to 10, and stirring at 60° C. for 10 h to obtain a silica sol;

[0103] S103, aging the sol for 24 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0104] S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 500° C. for 4 h to obtain biochar precursor powder;

[0105] S201. Modify the surface of biochar: Take 15 g of the biochar precursor powder obtained in S2, mix and stir with 150 mL of 0.1 mol / L potassium persulfate solution, stir at 60° C. for 4 h, wash and dry to obtain the modified biochar precursor powder.

[0106] S3, biochar deposition: 10 g of the modified biochar precursor powder obtained in S201 was dispersed in 60 mL of deionized water to form a biochar suspension, the silica sphere template was added to the biochar suspension, ultrasonically stirred for 4 h, dried at 90° C. for 12 h, and carbonized at 600° C. to obtain silica spheres covered with a biochar shell;

[0107] S4, removing the template: immersing the silica balls covered with the biochar shell layer in a 10 wt % hydrofluoric acid solution, standing at 25° C. for 0.8 h, filtering to obtain biochar solids, washing the biochar solids with deionized water, and drying to obtain biochar balls;

[0108] S5. Gallium oxide loading:

[0109] S501, preparing a gallium oxide precursor solution: dissolving 1 g of gallium nitrate in 40 mL of deionized water to obtain a gallium oxide precursor solution;

[0110] S502, immersing 5 g of biochar balls in 30 mL of the gallium oxide precursor solution, treating at 1000° C. for 4 h under a nitrogen atmosphere, to obtain gallium oxide-loaded biochar balls.

[0111] S6, Carbon quantum dot composite:

[0112] S601, preparing a CQDs solution: dissolving 10 mg of CQDs powder in 20 mL of deionized water to obtain a CQDs solution;

[0113] S602, ultrasonically mixing the gallium oxide-loaded biochar balls obtained in S502 with the CQDs solution for 2 hours, and drying at 80° C. to obtain a composite photocatalyst.

[0114] Example 3

[0115] The processing method provided in this embodiment includes the following steps:

[0116] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 3 hours. At the same time, an ultrasonic generator is used to emit ultrasonic waves to the wastewater to be treated, and the sound frequency of the ultrasonic generator is 100 kHz. The mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:800;

[0117] The preparation of the composite photocatalyst comprises the following steps:

[0118] S1. Provide silica sphere template:

[0119] S101, dissolving 10 mL of 1 mol / L tetraethyl orthosilicate in 100 mL of ethanol to obtain a transparent solution;

[0120] S102, adding ammonia water to the transparent solution, adjusting the pH to 9, stirring at 60° C. for 24 hours to obtain a silica sol;

[0121] S103, aging the sol for 36 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0122] S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 700° C. for 6 h to obtain biochar precursor powder;

[0123] S201. Modify the surface of biochar: Take 15 g of the biochar precursor powder obtained in S2, mix and stir with 150 mL of 0.1 mol / L potassium persulfate solution, stir at 60° C. for 6 h, wash and dry to obtain the modified biochar precursor powder.

[0124] Adding rice straw fiber to the modified biochar precursor powder:

[0125] The method for preparing the rice straw fiber comprises the following steps:

[0126] The rice straw fibers are cleaned and dried, and the dried rice straw fibers are ground to pass through a 200-mesh sieve to obtain pretreated rice straw fibers;

[0127] Pyrolyzing the pretreated rice straw fiber at 200° C. for 2 h in an oxygen-deficient environment to obtain rice straw fiber powder;

[0128] 3 g of rice straw fiber powder was mixed with 15 g of biochar precursor powder and stirred for 5 min to obtain a mixed precursor powder.

[0129] S3, biochar deposition: 10 g of the mixed precursor powder was dispersed in 60 mL of deionized water to form a biochar-plant fiber suspension, the silica sphere template was added to the biochar-plant fiber suspension, ultrasonically stirred for 6 h, dried at 100 ° C for 12 h, and carbonized at 900 ° C to obtain silica spheres covered with a biochar-plant fiber shell layer;

[0130] S4, removing the template: immersing the silica balls covered with the biochar-plant fiber shell layer in a 20 wt % hydrofluoric acid solution, standing at 25° C. for 1 hour, filtering to obtain biochar-plant fiber solids, washing the biochar-plant fiber solids with deionized water, and drying to obtain biochar-plant fiber balls;

[0131] S5. Gallium oxide loading:

[0132] S501, preparing a gallium oxide precursor solution: dissolving 1 g of gallium nitrate in 80 mL of deionized water to obtain a gallium oxide precursor solution;

[0133] S502, immersing 5 g of the biochar-plant fiber balls in 25 mL of the gallium oxide precursor solution, treating at 900° C. for 3.5 h under a nitrogen atmosphere, to obtain gallium oxide-loaded biochar-plant fiber balls.

[0134] S6, Carbon quantum dot composite:

[0135] S601, preparing a CQDs solution: dissolving 10 mg of CQDs powder in 15 mL of deionized water to obtain a CQDs solution;

[0136] S602, ultrasonically mixing the gallium oxide-loaded biochar-plant fiber balls obtained in S502 with the CQDs solution for 1 hour, and drying at 80° C. to obtain a composite photocatalyst.

[0137] Example 4

[0138] The processing method provided in this embodiment includes the following steps:

[0139] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 1.5 h. At the same time, an ultrasonic generator is used to emit ultrasonic waves to the wastewater to be treated, and the sound frequency of the ultrasonic generator is 20 kHz. The mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:200;

[0140] The preparation of the composite photocatalyst comprises the following steps:

[0141] S1. Provide silica sphere template:

[0142] S101, dissolving 10 mL of 1 mol / L tetraethyl orthosilicate in 100 mL of ethanol to obtain a transparent solution;

[0143] S102, adding ammonia water to the transparent solution, adjusting the pH to 11, and stirring at 60° C. for 6 hours to obtain a silica sol;

[0144] S103, aging the sol for 30 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0145] S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 700° C. for 5 h to obtain biochar precursor powder;

[0146] S201. Modify the surface of biochar: Take 20 g of the biochar precursor powder obtained in S2, mix and stir with 200 mL of 0.1 mol / L potassium persulfate solution, stir at 60° C. for 5 h, wash and dry to obtain the modified biochar precursor powder.

[0147] Adding rice straw fiber to the modified biochar precursor powder:

[0148] The preparation method of rice straw fiber comprises the following steps:

[0149] The rice straw fibers are cleaned and dried, and the dried rice straw fibers are ground to pass through a 200-mesh sieve to obtain pretreated rice straw fibers;

[0150] Pyrolyzing the pretreated rice straw fiber at 400° C. for 2 h in an oxygen-deficient environment to obtain rice straw fiber powder;

[0151] 4 g of rice straw fiber powder was mixed with 40 mL of 1 mmol / L hydrogen peroxide solution, stirred at 60° C. for 10 min, filtered, washed with deionized water, and dried to obtain modified rice straw fiber powder.

[0152] 2 g of modified rice straw fiber powder was mixed with 16 g of modified biochar precursor powder and stirred for 5 min to obtain a mixed precursor powder.

[0153] S3, biochar deposition: 10 g of the mixed precursor powder was dispersed in 60 mL of deionized water to form a biochar-plant fiber suspension, the silica sphere template was added to the biochar-plant fiber suspension, ultrasonically stirred for 5 h, dried at 80° C. for 12 h, and carbonized at 600° C. to obtain silica spheres covered with a biochar-plant fiber shell layer;

[0154] S4, removing the template: immersing the silica balls covered with the biochar-plant fiber shell layer in a 10 wt % hydrofluoric acid solution, standing at 25° C. for 1 hour, filtering to obtain biochar-plant fiber solids, washing the biochar-plant fiber solids with deionized water, and drying to obtain biochar-plant fiber balls;

[0155] S5. Gallium oxide loading:

[0156] S501, preparing a gallium oxide precursor solution: dissolving 1 g of gallium nitrate in 40 mL of deionized water to obtain a gallium oxide precursor solution;

[0157] S502, immersing 5 g of the biochar-plant fiber balls in 25 mL of the gallium oxide precursor solution, treating at 800° C. for 3 h under a nitrogen atmosphere, to obtain gallium oxide-loaded biochar-plant fiber balls.

[0158] S6, Carbon quantum dot composite:

[0159] S601, preparing a CQDs solution: dissolving 10 mg of CQDs powder in 20 mL of deionized water to obtain a CQDs solution;

[0160] S602, ultrasonically mixing the gallium oxide-loaded biochar-plant fiber balls obtained in S502 with the CQDs solution for 1 hour, and drying at 80° C. to obtain a composite photocatalyst.

[0161] Example 5

[0162] The processing method provided in this embodiment includes the following steps:

[0163] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 2 hours, and an ultrasonic generator is used to emit ultrasonic waves to the wastewater to be treated, wherein the ultrasonic generator has a sound frequency of 80 kHz, and the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:200;

[0164] The preparation of the composite photocatalyst comprises the following steps:

[0165] S1. Provide silica sphere template:

[0166] S101, dissolving 10 mL of 1 mol / L tetraethyl orthosilicate in 100 mL of ethanol to obtain a transparent solution;

[0167] S102, adding ammonia water to the transparent solution, adjusting the pH to 10, and stirring at 60° C. for 10 h to obtain a silica sol;

[0168] S103, aging the sol for 30 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

[0169] S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 700° C. for 5 h to obtain biochar precursor powder;

[0170] Adding rice straw fiber to the biochar precursor powder:

[0171] The method for preparing the rice straw fiber comprises the following steps:

[0172] The rice straw fibers are cleaned and dried, and the dried rice straw fibers are ground to pass through a 200-mesh sieve to obtain pretreated rice straw fibers;

[0173] Pyrolyzing the pretreated rice straw fiber at 300° C. for 2 h in an oxygen-deficient environment to obtain rice straw fiber powder;

[0174] 4 g of rice straw fiber powder was mixed with 40 mL of 1 mmol / L hydrogen peroxide solution, stirred at 60° C. for 10 min, filtered, washed with deionized water, and dried to obtain modified rice straw fiber powder.

[0175] 2 g of modified rice straw fiber powder was mixed with 14 g of biochar precursor powder and stirred for 5 min to obtain a mixed precursor powder.

[0176] S3, biochar deposition: 10 g of the mixed precursor powder was dispersed in 60 mL of deionized water to form a biochar-plant fiber suspension, the silica sphere template was added to the biochar-plant fiber suspension, ultrasonically stirred for 6 h, dried at 80° C. for 12 h, and carbonized at 600° C. to obtain silica spheres covered with a biochar-plant fiber shell layer;

[0177] S4, removing the template: immersing the silica balls covered with the biochar-plant fiber shell layer in a 10 wt % hydrofluoric acid solution, standing at 25° C. for 1 hour, filtering to obtain biochar-plant fiber solids, washing the biochar-plant fiber solids with deionized water, and drying to obtain biochar-plant fiber balls;

[0178] S5. Gallium oxide loading:

[0179] S501, preparing a gallium oxide precursor solution: dissolving 1 g of gallium nitrate in 40 mL of deionized water to obtain a gallium oxide precursor solution;

[0180] S502, immersing 5 g of the biochar-plant fiber balls in 25 mL of the gallium oxide precursor solution, treating at 800° C. for 3 h under a nitrogen atmosphere, to obtain gallium oxide-loaded biochar-plant fiber balls.

[0181] S6, Carbon quantum dot composite:

[0182] S601, preparing a CQDs solution: dissolving 10 mg of CQDs powder in 20 mL of deionized water to obtain a CQDs solution;

[0183] S602, ultrasonically mixing the gallium oxide-loaded biochar-plant fiber balls obtained in S502 with the CQDs solution for 1 hour, and drying at 80° C. to obtain a composite photocatalyst.

[0184] Comparative Example 1

[0185] The processing method provided in this comparative example comprises the following steps:

[0186] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 1.5 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:200.

[0187] The preparation process of the composite photocatalyst is the same as that of Example 4, but does not include S1 providing a silica sphere template, S3 biochar deposition, and S4 template removal.

[0188] Comparative Example 2

[0189] The processing method provided in this comparative example comprises the following steps:

[0190] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 1.5 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:200.

[0191] The preparation process of the composite photocatalyst is the same as that of Example 4, but does not include S5 gallium oxide loading.

[0192] Comparative Example 3

[0193] The processing method provided in this comparative example comprises the following steps:

[0194] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 1.5 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:200.

[0195] The preparation process of the composite photocatalyst is the same as that of Example 4, but does not include the S6 carbon quantum dot composite.

[0196] Comparative Example 4

[0197] The processing method provided in this comparative example comprises the following steps:

[0198] The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and the wastewater is treated under ultraviolet light of 250 nm for 1.5 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:200.

[0199] The preparation process of the composite photocatalyst is the same as that of Example 4, but does not include S1 providing a silica sphere template, S3 biochar deposition, S4 template removal, and S6 carbon quantum dot recombination.

[0200] Specifically, the preparation methods of the composite photocatalysts in Examples 1 to 5 are shown in Table 1.

[0201] Table 1 Preparation of composite photocatalysts of Examples 1 to 5

[0202]

[0203]

[0204] The preparation methods of the composite photocatalysts in Comparative Examples 1 to 4 are shown in Table 2.

[0205] Table 2 Preparation of composite photocatalysts in Comparative Examples 1 to 4

[0206]

[0207] Provide 5L and 50ng / L perfluorooctanoic acid solutions, and use the treatment methods of Examples 1 to 5 and Comparative Examples 1 to 4 to treat the perfluorooctanoic acid solutions, respectively. Take samples at 0.5h, 1h, 1.5h, and 2h, respectively, detect the perfluorooctanoic acid concentrations, and calculate the removal rate.

[0208] The removal rate test results are shown in Table 3 and Table 4. The mass ratio in Table 4 is the mass ratio of the composite photocatalyst to the organic wastewater.

[0209] Table 3 Final concentration of perfluorooctanoic acid before treatment and 2 hours after treatment in Examples 1 to 5 and Comparative Examples 1 to 4

[0210]

[0211]

[0212] Table 4 Removal of perfluorooctanoic acid by Examples 1 to 5 and Comparative Examples 1 to 4

[0213]

[0214] It can be known that the methods provided in Examples 4 and 5 of the present application and the composite photocatalysts used therein have a higher removal efficiency and a higher degradation rate (tending to be stable at about 1.5 hours). This is because the biochar is deposited on the surface of the silica sphere. After removing the silica sphere template, the biochar forms a hollow spherical structure, which provides sites for gallium oxide and carbon quantum dots. The synergistic effect of gallium oxide and carbon quantum dots is further enhanced in the hollow structure, thereby improving the photocatalytic performance. It itself has a larger internal space and reaction active sites (both the inner wall and the outer surface of the biochar sphere can provide sites), which is beneficial to the adsorption and degradation of pollutants. At the same time, the plant fiber (straw fiber) itself has porosity and a large specific surface area, which can also improve the mechanical strength of the biochar, making it more stable and durable, and increasing the number of cycles.

[0215] In the preferred treatment method for degrading perfluorooctanoic acid in water of the present application, the removal rate of perfluorooctanoic acid in wastewater can reach about 95%, and the composite photocatalyst has high mechanical strength and can be repeatedly used to reduce the treatment cost.

[0216] The present application also provides a treatment system for degrading perfluorooctanoic acid in water, see Figure 4 As shown, it includes a wastewater treatment device, which includes a wastewater treatment chamber for containing wastewater to be treated, a feeding module for adding a composite photocatalyst, a stirring module for stirring the wastewater, and an ultraviolet light module.

[0217] After the composite photocatalyst is added into the wastewater treatment chamber through the feeding module, the stirring module connected to the power supply is started, and continuous stirring is performed to fully mix the composite photocatalyst with the wastewater to be treated. The ultraviolet light module is used as a light source to make the composite photocatalyst react in the wastewater to be treated to degrade perfluorooctanoic acid.

[0218] Furthermore, the wastewater treatment device also includes an ultrasonic module, which is connected to the power supply. After the feeding module feeds the composite photocatalyst into the wastewater reaction chamber, the ultrasonic module emits ultrasonic waves to the wastewater to be treated for ultrasonic treatment.

[0219] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for degrading perfluorooctanoic acid in water, characterized in that: It includes the following steps: The wastewater to be treated containing perfluorooctanoic acid is introduced into a wastewater treatment device, a composite photocatalyst is added and stirred, and treated under ultraviolet light of 200 to 700 nm for 0.5 to 3 hours, wherein the mass volume ratio of the composite photocatalyst to the wastewater to be treated is 1:100 to 1:800; The preparation of the composite photocatalyst comprises the following steps: S1, providing a silica sphere template; S2. Preparation of biochar: using straw as raw material, washing, crushing and drying to obtain pretreated biomass raw material, and performing high temperature pyrolysis under anoxic conditions at 400-700° C. for 3-6 hours to obtain biochar precursor powder; Adding straw fiber to the biochar precursor powder, the preparation method of the straw fiber comprises: The rice straw fibers are cleaned and dried, and the dried rice straw fibers are ground to pass through a 200-mesh sieve to obtain pretreated rice straw fibers; Pyrolyzing the pretreated rice straw fiber at a high temperature of 200-400° C. for 2 h in an oxygen-deficient environment to obtain rice straw fiber powder; Modification of the rice straw fiber: The rice straw fiber powder was mixed with 1 mmol / L hydrogen peroxide solution at a mass volume ratio of 1:10, stirred at 60° C. for 10 min, filtered, washed with deionized water, and dried to obtain modified rice straw fiber powder; The modified rice straw fiber powder and the biochar precursor powder are mixed in a mass ratio of 1:5 to 1:8, and stirred for 5 minutes to obtain a mixed precursor powder; S3, biochar deposition: dispersing the mixed precursor powder in deionized water at a mass volume ratio of 1:6 to form a biochar suspension, adding the silica sphere template to the biochar suspension, ultrasonically stirring for 3 to 6 hours, drying at 80 to 100° C. for 12 hours, and carbonizing at 500-900° C. to obtain silica spheres covered with a biochar shell; S4, removing the template: immersing the silica balls covered with the biochar shell layer in a 8-20 wt% hydrofluoric acid solution, standing at 25° C. for 0.5-1 h, filtering to obtain biochar solids, washing the biochar solids with deionized water, and drying to obtain biochar balls; S5. Gallium oxide loading: S501, preparing a gallium oxide precursor solution: dissolving gallium nitrate in deionized water at a mass volume ratio of 1:20 to 1:80 to obtain a gallium oxide precursor solution; S502, immersing the biochar balls in a gallium oxide precursor solution at a mass volume ratio of 1:3 to 1:6, and treating at 800 to 1000° C. for 3 to 4 hours under a nitrogen atmosphere to obtain gallium oxide-loaded biochar balls; S6, Carbon quantum dot composite: Preparation of CQDs solution: adding CQDs powder into deionized water at a mass volume ratio of 1:1 to 1:2 to obtain a CQDs solution; The gallium oxide-loaded biochar balls and the CQDs solution are ultrasonically mixed for 0.5 to 2 hours, and dried at 80° C. to obtain a composite photocatalyst.

2. The method for degrading perfluorooctanoic acid in water according to claim 1, characterized in that: In S1, the preparation of silica spheres comprises the following steps: S101, dissolving 0.5-1 mol / L of ethyl orthosilicate in ethanol at a ratio of 1:10 to obtain a transparent solution; S102, adding ammonia water to the transparent solution, adjusting the pH to 9-11, stirring at 60° C. for 6-24 hours to obtain a silica sol; S103, aging the sol for 24 to 36 hours, washing after centrifugation, and drying the obtained solid at 80° C. for 12 hours to obtain a silica sphere template.

3. The method for degrading perfluorooctanoic acid in water according to claim 1, characterized in that: The S2 further comprises the following steps: S201. Modifying the surface of biochar: mixing the biochar precursor powder with 0.1 mol / L potassium persulfate solution at a mass volume ratio of 1:10 and stirring, stirring at 60° C. for 4 to 6 hours, washing and drying to obtain a modified biochar precursor powder.

4. The method for degrading perfluorooctanoic acid in water according to claim 1, characterized in that: The S2 further includes: The biochar precursor powder was passed through a 200-mesh sieve.

5. The method for degrading perfluorooctanoic acid in water according to claim 1, characterized in that: When the composite photocatalyst is added, an ultrasonic generator is used to emit ultrasonic waves to the wastewater to be treated for ultrasonic treatment, and the sound frequency of the ultrasonic generator is 20 to 100 kHz.

6. A treatment system for degrading perfluorooctanoic acid in water, used for any one of the treatment methods for degrading perfluorooctanoic acid in water as claimed in claims 1 to 5, characterized in that: It includes: The wastewater treatment device comprises a wastewater treatment chamber for containing wastewater to be treated, a feeding module for adding a composite photocatalyst, a stirring module for stirring the wastewater, and an ultraviolet light module, wherein the feeding module, the stirring module and the ultraviolet light module are connected to a power source.

7. The treatment system for degrading perfluorooctanoic acid in water according to claim 6, characterized in that: The wastewater treatment device further comprises an ultrasonic module, and the ultrasonic module is connected to the power supply.

Citation Information

Patent Citations

  • Hollow porous carbon nitride nanospheres composite loaded with agbr nanoparticles, preparation method thereof, and its application in dye degradation

    US20190126257A1

  • Compositions and methods for removal of per- and polyfluoroalkyl substances (PFAS)

    US20210206670A1